Analisis Pengaruh Price To Book Value, Current Ratio, Tingkat Suku Bunga dan Ukuran Perusahaan Terhadap Return Saham Pada Perusahaan yang Terdaftar di Indeks Kompas 100 Periode 2012-2016 - Aulia Nisa; Khairunnisa Khairunnisa (Universitas Putera Batam, 2019)
Stock return is an advantage received by investors for stock investment. The stock return of the Kompas 100 Index in 2012-2016 has fluctuated, so that it causes uncertainty that will be obtained by investors when carrying out stock investments in a company. This study aims to determine and analyze the effect of price to book value, current ratio, interest rates and company size on stock returns in companies listed in the Kompas 100 Index in 2012-2016. The analytical method used in the research is panel data regression. The results of this study indicate that the interest rate variable partially has a significant effect on stock returns. The price to book value, current ratio, and company size variables partially do not have a significant effect on stock returns. Simultaneously, the price to book value, current ratio, interest rates and company size variables have a significant influence on stock returns.